Comparison of the Therapeutic Effects of Topiramate and Phenobarbital on the Quality of Life of Children under Five with Fever and Convulsion - Hamid Talebianpour; Elham Talebianpour; Hamid Nemati; Khosro Keshavarz (Kerman University of Medical Sciences, 2019)
Comparison of the Therapeutic Effects of Topiramate and Phenobarbital on the Quality of Life of Children under Five with Fever and Convulsion   Talebianpour Hamid 1, Talebianpour Elham 2, Nemati Hamid 3, Keshavarz Khosro 4* 1. PhD Student in Health Economics, Student Research Committee, Tehran University of Medical Sciences, Tehran, Iran 2. MSc Student in Nursing, Student Research Committee, Yasuj University of Medical Sciences, Yasuj, Iran 3. Assistant Professor of Pharmacoeconomics and Pharmaceutical Administration, Health Human Resources Research Center, School of Management & Medical Informatics, Shiraz University of Medical Sciences, Shiraz, Iran 4. Assistant Professor of Pediatric Neurology, Neuroscience Research Center, Shiraz University of Medical Sciences, Shiraz, Iran * Corresponding Author: Khosro Keshavarz Address: Alley 29, Qasr al-Dasht Street Molla Sadra Intersection, Shiraz Tel: 00987132340774                                               Email: khkeshavarz2007@gmail.com Abstract: Background & Objectives: Failure to treat febrile seizure in children leads to physical, psychological and social problems and if not treated timely, might lead to epilepsy which affects the quality of life of children. The purpose of this study was to compare the therapeutic effects of two drugs on the quality of life of children under five with febrile convulsion. Methods: This was a descriptive-analytical study that was done in an interventional manner. In this study, the quality of life of 40 children with febrile convulsion treated with topiramate and 51 children who had the same problem and treated with phenobarbital drug were compared. Data collection tool was EQ5D questionnaire. ANOVA and t-test were used for statistical analysis and data were entered into SPSS statistical software version 22. Results: Mean scores of quality of life in children taking phenobarbital and topiramate were 72.5 and 82.7, respectively. Topiramate had a significant effect on the mean score of quality of life in children with febrile convulsion and increased it. Parental education and early febrile convulsion had a significant relationship with patients' quality of life.  Conclusion: Health policy makers, physicians, and other members of health care system must provide access to appropriate educational, medical, and therapeutic services for children with febrile seizure in order to improve their health status.   Keywords: Febrile convulsion, Topiramate, Phenobarbital, Quality of Life, Children   Citation: Talebianpour H, Talebianpour E, Nemati H, Keshavarz K. Comparison of the Therapeutic Effects of Topiramate and Phenobarbital on the Quality of Life of Children under Five with Fever and Convulsion. Journal of Health Based Research 2019; 5(3): 261-72.